Analisis Faktor-Faktor Kesiapan Kerja di Bidang Kuliner pada Siswa Sekolah Menengah Kejuruan - Nadia Melinia; Siti Mariah (Jurnal Pendidikan, 2022)
This study aims to determine the factors of job readiness in the culinary field. This research is a quantitative research. Data collection techniques used questionnaires and documentation. The validity of the items was tested with the product moment correlation, the results obtained were 19 valid items and 3 items failed. The results of the reliability test obtained the value of Alpha = 0.951. Data analysis techniques in this study are the mean, median, mode, and standard deviation. The results showed that the factors of job readiness in the culinary field in Vocational High School students were in the sufficient category with a relative frequency of 60.32%. The variables of job readiness factors in the culinary field have two indicators, namely internal factors and external factors. (1) Internal factors are in sufficient category with a relative frequency of 66.67% and (2) external factors are in sufficient category with a relative frequency of 52.38%. It can be concluded that the internal and external factors of work readiness in the culinary field are quite sufficient. Students are expected to be more active and confident in learning theory and practice.